2022
DOI: 10.3390/s22197382
|View full text |Cite
|
Sign up to set email alerts
|

Computational Optimization of Image-Based Reinforcement Learning for Robotics

Abstract: The robotics field has been deeply influenced by the advent of deep learning. In recent years, this trend has been characterized by the adoption of large, pretrained models for robotic use cases, which are not compatible with the computational hardware available in robotic systems. Moreover, such large, computationally intensive models impede the low-latency execution which is required for many closed-loop control systems. In this work, we propose different strategies for improving the computational efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Whether an agent maintains a simple continuous generative model or makes use of a higher-level discrete model for planning, to operate in realistic scenarios it needs the notion of environmental beliefs . Maintaining additional beliefs over the environment has been used for actively inferring object-centric representations [41], and we here turn to the problem of tackling dynamic tasks that comprise multiple steps or composite movements. If the agent’s goal is to reach a moving object, it must maintain not only a best guess about its hand position, but also about the object position [42].…”
Section: Resultsmentioning
confidence: 99%
“…Whether an agent maintains a simple continuous generative model or makes use of a higher-level discrete model for planning, to operate in realistic scenarios it needs the notion of environmental beliefs . Maintaining additional beliefs over the environment has been used for actively inferring object-centric representations [41], and we here turn to the problem of tackling dynamic tasks that comprise multiple steps or composite movements. If the agent’s goal is to reach a moving object, it must maintain not only a best guess about its hand position, but also about the object position [42].…”
Section: Resultsmentioning
confidence: 99%
“…This nuanced understanding is vital in comparing the processing speeds of QFR, OFR, CT-FFR, and iFR [ 39 ]. Deep learning models can perform a large number of matrix operations in parallel on GPUs, thereby improving the computational efficiency and accuracy [ 40 ]. However, some studies have also pointed out that the computational speed of QFR and OFR is also improving, and the results can be obtained within a few minutes by optimizing the algorithm and platform, and no additional equipment and software are required [ 41 ].…”
Section: Discussion: Comprehensive Evaluation Of Computational Hemody...mentioning
confidence: 99%
“…In the equivariant representation, the transformation to the input observation is preserved and cascaded into the intermediate space. Equivariant representations have been highly adopted in the context of machine learning [15,24–26], and are considered crucial to achieving generalization features from the model at hand. The adoption of equivariant architectures is favoured in the research of ‘disentangled’ systems by the machine learning community where they have demonstrated their efficiency in generalization, imagination and abstraction reasoning.…”
Section: Discussionmentioning
confidence: 99%